2004
DOI: 10.1007/s00109-004-0582-8
|View full text |Cite
|
Sign up to set email alerts
|

Activation of cardiac human ether-a-go-go related gene potassium currents is regulated by ?1A-adrenoceptors

Abstract: Patients with cardiac disease typically develop life-threatening ventricular arrhythmias during physical or emotional stress, suggesting a link between adrenergic stimulation and regulation of the cardiac action potential. Human ether-a-go-go related gene (hERG) potassium channels conduct the rapid component of the repolarizing delayed rectifier potassium current, I(Kr). Previous studies have revealed that hERG channel activation is modulated by activation of the beta-adrenergic system. In contrast, the influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 33 publications
4
32
0
1
Order By: Relevance
“…The hERG potassium channel has been reported to be regulated by a number of intracellular molecules and pathways, including cAMP and protein kinase A (Thomas et al, 1999;Cui et al, 2000), protein kinase C (Barros et al, 1998;Thomas et al, 2004), phospholipase C (Bian et al, 2001(Bian et al, , 2004Gomez-Varela et al, 2003), and Src tyrosine kinase (Cayabyab and Schlichter, 2002). Increase of the hERG current can be induced by the substrate of phospholipase C, phosphatidylinositol 4,5-bisphosphate (Bian et al, 2001(Bian et al, , 2004, activation of Src tyrosine kinase (Cayabyab and Schlichter, 2002), and perhaps by modulations of other pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The hERG potassium channel has been reported to be regulated by a number of intracellular molecules and pathways, including cAMP and protein kinase A (Thomas et al, 1999;Cui et al, 2000), protein kinase C (Barros et al, 1998;Thomas et al, 2004), phospholipase C (Bian et al, 2001(Bian et al, , 2004Gomez-Varela et al, 2003), and Src tyrosine kinase (Cayabyab and Schlichter, 2002). Increase of the hERG current can be induced by the substrate of phospholipase C, phosphatidylinositol 4,5-bisphosphate (Bian et al, 2001(Bian et al, , 2004, activation of Src tyrosine kinase (Cayabyab and Schlichter, 2002), and perhaps by modulations of other pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The unique features of muscarinic modulation of ERG K ϩ currents in ICC may be due to the fact that we recorded from native cells, whereas most if not all reported studies on muscarinic regulation in the literature have been conducted using coexpression of both G-protein-coupled receptors and HERG/ERG K ϩ channels in expression systems (e.g., Xenopus oocytes, rat GH 3 /B 6 , Chinese hamster ovary, human embryonic kidney 293, human tsA-201) (Barros et al, 1998;Kiehn et al, 1998;Cui et al, 2000;Bian et al, 2001;Schledermann et al, 2001;Thomas et al, 2003Thomas et al, , 2004Hirdes et al, 2004). Another possible explanation is that in ICC, the ERG K ϩ channel may be coexpressed with ␤-subunits (minK or MiRP1), which have been found to coexpress with HERG K ϩ channels in native tissue and have been shown to influence HERG K ϩ channel properties (McDonald et al, 1997;Abbott et al, 1999;Weerapura et al, 2002).…”
Section: Muscarinic Regulation Of Erg Kmentioning
confidence: 99%
“…Barros et al (1998) and Thomas et al (2003Thomas et al ( , 2004 have reported HERG K ϩ current modulation via a PKC-dependent mechanism based on experiments using PKC activation and inhibition in Xenopus oocytes expressing HERG K ϩ channel protein. Although it was hypothesized that PKC modulated HERG K ϩ channels by phosphorylation of PKC-dependent phosphorylation sites, deletion of these sites by mutagenesis did not prevent the response to G-protein receptor agonists or PKC activators (Thomas et al, 2003(Thomas et al, , 2004. To date, the phosphorylation-independent mechanism responsible for PKC dependent modulation remains unknown.…”
Section: Muscarinic Regulation Of Erg Kmentioning
confidence: 99%
See 1 more Smart Citation
“…In the ventricular myocardium of most mammalian species, including dog and human, delayed rectifier K + current is composed of two independent components, called I Kr and I Ks (Gintant 1996, Li et al 1996. Both components are known to be under the control of the cAMP/PKA pathway, while the role of PKC in regulation of I Kr and I Ks is controversial, and therefore, poorly understood in spite of the extensive investigations of the field (Tohse 1990, Xiao et al 2003, Thomas et al 2004a, Toda et al 2007, Matavel and Lopes 2009. Appropriate approach of this problem might be the application of selective PKC inhibitors, provided that these agents fail to interact directly with the ion channels mediating delayed rectifier K + currents.…”
Section: Introductionmentioning
confidence: 99%